Humanistic Leadership and Job Satisfaction Among Health Sciences Lecturers: The Mediating Role of Meaningful Work - Putria Carolina (Nursing and Health Sciences Journal (NHSJ), 2026)
Introduction: Health sciences Lecturers are increasingly confronted with complex professional demands, including the integration of teaching, research, and community service responsibilities, which place substantial pressure on their well-being and job satisfaction. In this context, job satisfaction emerges as a critical factor in sustaining academic performance, professional commitment, and institutional effectiveness. Leadership practices, particularly humanistic leadership, are considered pivotal in shaping positive work environments that acknowledge lecturers’ values, dignity, and professional contributions. This study, therefore, examines the effect of humanistic leadership on health lecturers’ job satisfaction, with meaningful work positioned as a mediating mechanism. Method: This research employed a quantitative explanatory design. Data were collected through a structured questionnaire from 105 health sciences lecturers at private higher education institutions in Palangka Raya City using purposive sampling. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that humanistic leadership has a significant and substantial effect on lecturers’ job satisfaction. In addition, humanistic leadership positively influences meaningful work. The mediation analysis demonstrates that meaningful work partially mediates the relationship between humanistic leadership and job satisfaction, although the indirect effect is smaller than the direct effect of leadership. Result: These results suggest that leadership practices emphasizing human dignity, fair interpersonal relationships, and support for professional development contribute directly to higher job satisfaction while also fostering a more meaningful work experience. Conclusion: The study contributes to the literature by providing empirical evidence on the role of humanistic leadership and meaningful work in the context of Indonesian private higher education. Practically, the findings highlight the importance of strengthening humanistic leadership practices to enhance lecturers’ job satisfaction and support sustainable performance in health higher education institutions.